2019
DOI: 10.1038/s41598-019-40653-z
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamin D and Adrenal Parameters with Metabolic and Inflammatory Markers in Polycystic Ovary Syndrome

Abstract: Vitamin D deficiency has been related with metabolic alterations in polycystic ovary syndrome (PCOS). As well, hyperactivation of adrenal axis can be programmed early in life and could be related later with PCOS development. Our aim was to establish the relationship between vitamin D and adrenal parameters with metabolic alterations and inflammation markers in PCOS. In 73 patients and 33 controls, 25-hydroxyvitamin D (25-OH-D), total and bioavailable testosterone (TT and bioT), androstenedione (A4), SHBG, cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
3
12
1
Order By: Relevance
“…Previous studies have shown inconsistent results in terms of vitamin D levels in PCOS women, which have mainly been in opposition with the present results [16,44,46], although this has not been the case in all studies [9,45]. Studies reporting lower vitamin D levels in women with PCOS have been conducted with fairly small sample sizes, recruiting cases from infertility clinics without considering substantive confounding factors [9,16,46]. Recent studies suggest that lower 25(OH)D levels are associated with prolonged menstrual cycles in healthy women [47] and that vitamin D supplementation promotes follicle development and restores menstrual cycles in women with PCOS [6,48].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown inconsistent results in terms of vitamin D levels in PCOS women, which have mainly been in opposition with the present results [16,44,46], although this has not been the case in all studies [9,45]. Studies reporting lower vitamin D levels in women with PCOS have been conducted with fairly small sample sizes, recruiting cases from infertility clinics without considering substantive confounding factors [9,16,46]. Recent studies suggest that lower 25(OH)D levels are associated with prolonged menstrual cycles in healthy women [47] and that vitamin D supplementation promotes follicle development and restores menstrual cycles in women with PCOS [6,48].…”
Section: Discussioncontrasting
confidence: 99%
“…Elevated androgen levels in PCOS cause unfavorable derangements in adipose tissue and in glucose metabolism [16]. It has been proposed that the connection between vitamin D and PCOS arises from the endocrine pathways affected in PCOS, such as sex hormone synthesis and insulin secretion [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we used waist circumference as an indicator of visceral adiposity, which was positively associated with hsCRP, HOMA and HbA1C in women with PCOS. This is in keeping with another study which found a positive association between hsCRP and waist circumference in women with PCOS [31]. We also found a negative correlation between hsCRP and %ASM in women with PCOS which is consistent with studies in older adults [27] and obese individuals [32].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, plasma 25-hydroxyvitamin D correlated positively with %ASM and negatively with waist circumference in women with PCOS. These results are consistent with others who have demonstrated a positive association between vitamin D and percent lean mass in obese individuals [32] and a negative association between vitamin D and waist circumference in women with PCOS [31]. Furthermore, vitamin D remains positively associated with skeletal muscle mass after adjusting for body fat mass in obese individuals [39].…”
Section: Discussionsupporting
confidence: 92%
“…Mean ± SD CRP values were not provided in 22 studies [ 42 , 46 , 60 , 62 , 63 , 65 , 66 , 68 , 72 , 73 , 78 , 82 , 83 , 92 , 93 , 99 , 108 , 110 , 112 , 118 , 119 , 121 ]. Authors of these articles were contacted to provide the missing data, but no response was received despite several reminders.…”
Section: Resultsmentioning
confidence: 99%